2014
DOI: 10.1126/science.1254721
|View full text |Cite
|
Sign up to set email alerts
|

Patient-derived models of acquired resistance can identify effective drug combinations for cancer

Abstract: Targeted cancer therapies have produced substantial clinical responses but most tumors develop resistance to these drugs. Here we describe a pharmacogenomic platform that facilitates rapid discovery of drug combinations that can overcome resistance. We established cell culture models derived from biopsy samples of lung cancer patients whose disease had progressed while on treatment with EGFR or ALK tyrosine kinase inhibitors and then subjected these cells to genetic analyses and a pharmacological screen. Multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
611
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 667 publications
(624 citation statements)
references
References 36 publications
13
611
0
Order By: Relevance
“…Studies that report normal epithelial cell expansion have tended to initiate culture from early‐stage primary NSCLC tumors, whereas studies in which cancer cells have been expanded have initiated culture using biopsies or effusions from patients with late‐stage, therapy‐resistant disease7, 8, 9 or from PDX models,24 which may be more aggressive and/or more adaptable to cell culture. This would be consistent with traditional NSCLC cell culture methods and PDX models, where patient models are more readily established from late‐stage, metastatic or therapy‐resistant disease than from early‐stage primary disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that report normal epithelial cell expansion have tended to initiate culture from early‐stage primary NSCLC tumors, whereas studies in which cancer cells have been expanded have initiated culture using biopsies or effusions from patients with late‐stage, therapy‐resistant disease7, 8, 9 or from PDX models,24 which may be more aggressive and/or more adaptable to cell culture. This would be consistent with traditional NSCLC cell culture methods and PDX models, where patient models are more readily established from late‐stage, metastatic or therapy‐resistant disease than from early‐stage primary disease.…”
Section: Discussionmentioning
confidence: 99%
“…Protocol differences exist between the aforementioned studies: key studies have used inactivated human dermal fibroblasts7, 8 as feeder layers rather than the mouse embryonic fibroblasts often used in those that see normal cell expansion and it has also been possible to transition tumor cell cultures off feeder layers after 6 months of culture establishment 8. We have previously demonstrated that adult human lung fibroblasts do not support long‐term normal airway epithelial cell expansion in the same way as 3T3‐J2 cells17 so the use of adult and/or human feeder cells might favor tumor cell expansion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Src regulates many fundamental cellular processes, including cell growth, differentiation, migration, and drug resistance (22,(29)(30)(31)(32). In our study, acquisition of acquired resistance to dovitinib is attributable to the activation of a Src-driven bypass signaling pathway.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies have demonstrated that Src sits on the signaling node mediating resistance to multiple anticancer agents (22). The increased activation of Src led us to hypothesize that Src activation directly mediated acquired resistance to dovitinib in LC-2/ad DR cells.…”
Section: Activation Of Src Mediates Acquired Resistance To Dovitinib mentioning
confidence: 99%